Between‐day reliability of local thermal hyperemia in the forearm and index finger using single‐point laser Doppler flowmetry. (6th November 2017) - McGarr, Gregory W.; Hodges, Gary J.; Cheung, Stephen S.
Abstract: Objective: To assess between‐day reliability for LTH in glabrous and nonglabrous index finger skin and nonglabrous forearm skin, with single‐point laser Doppler flowmetry. Methods: Part‐1: In healthy, habitually active males (n=10), LTH was examined twice ( 7‐10 days apart) for both skin types on the index finger. Part‐2: Identical testing was performed on the volar forearm. Local heating (33‐42°C at 1°C·20 s −1 + 20 minutes at 44°C) was performed at all skin sites and baseline, initial peak, and plateau phases were identified. Data were expressed as raw CVC (laser‐Doppler flux/MAP), and as CVC normalized to baseline (%CVC33°C ) and maximum heating (%CVC44°C ). Reliability was assessed using between‐day mean difference, %CV, and ICC. Results: Reliability (%CV) was poor at baseline for all forms of data presentation and for other phases with %CVC33°C . At the initial peak and plateau, reliability was moderate‐poor (20%‐26%) for CVC and good‐moderate (6%‐18%) for %CVC44°C . Reliability was good‐moderate for vasodilatory onset time (10%‐23%) and time to initial peak (6%‐13%). Conclusions: For all sites, LTH reliability was acceptable for the timing, and for the initial peak and plateau using CVC or %CVC44°C .